2022
DOI: 10.1021/acs.energyfuels.2c01943
|View full text |Cite
|
Sign up to set email alerts
|

Fabrications and Applications of Micro/Nanofluidics in Oil and Gas Recovery: A Comprehensive Review

Abstract: Understanding fluid flow characteristics in porous medium, which determines the development of oil and gas oilfields, has been a significant research subject for decades. Although using core samples is still essential, micro/nanofluidics have been attracting increasing attention in oil recovery fields since it offers direct visualization and quantification of fluid flow at the pore level. This work provides the latest techniques and development history of micro/nanofluidics in oil and gas recovery by summarizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 235 publications
0
2
0
Order By: Relevance
“…The commonly used nanomaterials in the field of oil/gas exploration and development include SiO 2 , NiO, Fe 3 O 4 , nano-polymer microspheres, etc. Among them, nano SiO 2 is the most widely used due to its excellent performance, good universality, and low comprehensive cost [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used nanomaterials in the field of oil/gas exploration and development include SiO 2 , NiO, Fe 3 O 4 , nano-polymer microspheres, etc. Among them, nano SiO 2 is the most widely used due to its excellent performance, good universality, and low comprehensive cost [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To study the flow characteristic and EOR mechanism of polymer microspheres more comprehensively, microfluidic models were developed to visualize the microscopic flow mechanisms of the polymer microspheres in porous media. Ghosh and Mohanty reported that polymer solutions can improve filtration and transport capacity in low-permeability porous media and improve the sweep efficiency of the EOR process. Based on the visualization model of a microfluidic chip, Baiyu et al established a set of methods to evaluate the effect of particle plugging in a fracture-vuggy reservoir.…”
Section: Introductionmentioning
confidence: 99%